Implementation of Asset Based Community Development (Asset-Based Community Development) on MGMP Geografi SMA Karawang Regency - Halimatusha'diah, Halimatusha'diah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The aim of this research is to determine the implementation of asset-based community development in an effort to maintain the sustainability of MGMP Geografi SMA Kabupaten Karawang. This research uses descriptive qualitative with a case study approach. The data collection technique used was through interviews and documentation studies. The data analysis techniques used are through the stages of data triangulation, data reduction, and drawing conclusions. The results of this research indicate that the implementation of asset-based community development at MGMP Geografi SMA Kabupaten Karawang was carried out as an effort to overcome various limitations and obstacles that occur in this organization, namely low member participation, low member motivation, and threatening the sustainability of the MGMP organization in the future. By implementing asset-based community development, this organization has succeeded in remaining active, the organization's work program continues to be implemented, and the organization's activities run well, despite various existing limitations.